Alterations in high-density lipoprotein proteome and function associated with persistent organic pollutants. (January 2017) - Ljunggren, Stefan A.; Helmfrid, Ingela; Norinder, Ulf; Fredriksson, Mats; Wingren, Gun; Karlsson, Helen; Lindahl, Mats
Abstract: There is a growing body of evidence that persistent organic pollutants (POPs) may increase the risk for cardiovascular disease (CVD), but the mechanisms remain unclear. High-density lipoprotein (HDL) acts protective against CVD by different processes, and we have earlier found that HDL from subjects with CVD contains higher levels of POPs than healthy controls. In the present study, we have expanded analyses on the same individuals living in a contaminated community and investigated the relationship between the HDL POP levels and protein composition/function. HDL from 17 subjects was isolated by ultracentrifugation. HDL protein composition, using nanoliquid chromatography tandem mass spectrometry, and antioxidant activity were analyzed. The associations of 16 POPs, including polychlorinated biphenyls (PCBs) and organochlorine pesticides, with HDL proteins/functions were investigated by partial least square and multiple linear regression analysis. Proteomic analyses identified 118 HDL proteins, of which ten were significantly (p < 0.05) and positively associated with the combined level of POPs or with highly chlorinated PCB congeners. Among these, cholesteryl ester transfer protein and phospholipid transfer protein, as well as the inflammatory marker serum amyloid A, were found. The serum paraoxonase/arylesterase 1 activity was inversely associated with POPs. Pathway analysis demonstrated that up-regulated proteins were associated with biological processes involving lipoprotein metabolism, while down-regulated proteins were associated with processes such as negative regulation of proteinases, acute phase response, platelet degranulation, and complement activation. These results indicate an association between POP levels, especially highly chlorinated PCBs, and HDL protein alterations that may result in a less functional particle. Further studies are needed to determine causality and the importance of other environmental factors. Nevertheless, this study provides a first insight into a possible link between exposure to POPs and risk of CVD. Graphical abstract: Highlights: Persistent organic pollutants (POPs) were associated with changes in HDL proteome. Up-regulated proteins were involved in HDL lipoprotein metabolic processes. Down-regulated proteins were involved in several protective functions of HDL. POPs were associated with markers of dysfunctional HDL.